2014
DOI: 10.1074/jbc.m114.572461
|View full text |Cite
|
Sign up to set email alerts
|

Myopathy-causing Mutations in an HSP40 Chaperone Disrupt Processing of Specific Client Conformers

Abstract: Background: Mutations in the G/F domain of the human HSP40 chaperone DNAJB6 cause a protein aggregate myopathy. Results: Homologous mutations in the yeast HSP40 Sis1 alter prion propagation in a prion strain-dependent manner. Conclusion: G/F domain mutations affect chaperone-mediated processing of particular client conformers. Significance: Impaired processing of certain substrate conformations may be one mechanism that contributes to chaperonopathy pathogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
103
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 53 publications
(107 citation statements)
references
References 48 publications
4
103
0
Order By: Relevance
“…As we found previously, deletion of the G/F region eliminated the propagation of all five [ RNQ +] variants (Fig. C and Stein et al ., ). Interestingly, other than Sis1‐ΔG/F, both s.d.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…As we found previously, deletion of the G/F region eliminated the propagation of all five [ RNQ +] variants (Fig. C and Stein et al ., ). Interestingly, other than Sis1‐ΔG/F, both s.d.…”
Section: Resultsmentioning
confidence: 97%
“…Previous work has focused on the fact that different prions, or prion variants, show distinct sensitivity to chaperone levels (Fan et al ., ; Hines and Craig, ; Hines et al ., ). We have recently shown that the propagation of several different [ RNQ +] variants all require the presence of the Sis1 G/F region, while [ PSI +] variants show differential dependence on this region (Stein et al ., ). Here, we show that other domains of Sis1 are also important for substrate recognition or processing in a prion variant‐dependent manner.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…The Hsp70 recruitment ability of DNAJB6 was disrupted by replacing its J-domain HPD motif with an AAA sequence. DnaJB6 is mutated in inherited myofibrillar myopathy and limb-girdle muscular dystrophy (Stein et al, 2014), and we also tested the effect of a disease-linked DnaJB6b mutation on DENV replication (Fig. 6G, S5D, F93L).…”
Section: Resultsmentioning
confidence: 99%